Empowerment and Improvement of Mustahiq's Independence to Become Muzakki - Husnul Khatimah; Nuradi Nuradi (LAA MAISYIR: Jurnal Ekonomi Islam, 2020)
Aim of the research is to find how to empowerment and improve the independence of mustahiq to become muzakki in Baznas Sukabumi Regency. Approachment that used by researchers is quantitative approach with Partial Least Square (PLS) analysis, which is an alternative method of SEM (Structural Equation Modelling) in analyzing factors that affect the level of independence of mustahiq's business by using the case study method or field research. The results of this study indicate that the successful of the empowerment and improvement of independence programs from mustahiq to new muzakki has reached the level of making them munfiq, this is a quite encouraging result considering the economic limitations with little business capital and income, however, they have routinely put their donations into the Gathering Council of Zakat/Dewan Pengumpul Zakat (DPZ) of mosque that around of their living.